Estrutura da comunidade de peixes em poças de maré de praias arenosas regidas por macromarés no litoral equatorial amazônico, Maranhão – Brasil - CARVALHO, Glínia Kelle Fernandes Coelho de (2013)
The present study was conducted in tide pools found in ferruginous sandstone outcrops in the intertidal zone of Araçagy Beach and rocky outcrops on Panaquatira Beach, both of which are found on Maranhão Island, northeastern Brazil. The aim was to describe aspects of the structure and spatiotemporal distribution of the fish community in tide pools on sandy beaches in order to contribute to the understanding of the influence of macrotides and estuaries on this community. The intertidal zone of both beaches was divided into three distinct tiers and three tide pools from each tier were selected for sampling. The tide pools were not connected to the ocean or two other tide pools at low tide. Sampling was performed every two months from August 2011 to June 2012, using a menthol ethyl alcohol solution at a proportion of 40 g/L as anesthesia for the fish, especially cryptic and den-dwelling species. At each pool, data were collected on surface area, volume, mean depth, roughness and abiotic variables (temperature, salinity, dissolved oxygen and pH), using a standard methodology. A total of 1780 fish were collected, 39% of which were collected from Araçagy Beach and 61% were collected from Panaquatira Beach. Species richness and abundance were influenced by the adjacent environments and morphometry of the tide pools, for which surface area and depth were the most important aspects to the variation in physicochemical parameters. Clear differences were evidenced between seasons and tiers of the intertidal zone, with environmental variables fluctuating throughout the year and between tiers. The tide pools were dominated by small, well- camouflaged, resident species. However, juveniles of transitory and occasional species were also observed, including economically important species such as mullets (Mugilidae), snappers (Lutjanidae) and grunts (Haemulidae). Future studies on intertidal fish communities should focus on the reproductive biology, ecology and biogeography of these species to contribute more robust findings regarding the importance of tide pools to the lifecycle of these fish.